Hubungan antara kemandirian belajar dengan hasil belajar matematika - Maria Florentina Woi; Yuli Prihatni (Research and Social Study Institute, 2019)
Tujuan penelitian ini adalah untuk mengetahui hubungan antara kemandirian belajar dengan hasil belajar matematika siswa kelas VII SMPN 3 Berbah. Penelitian ini termasuk penelitian kuantitatif. Populasi dalam penelitian ini adalah seluruh kelas VII SMPN 3 Berbah yang berjumlah 4 kelas dengan total siswa sebanyak 127 orang. Sampel dalam penelitian ini sebanyak 96 orang. Teknik pengambilan sampel menggunakan simple random sampling. Teknik pengumpulan data menggunakan angket dan dokumentasi. Uji hipotesis menggunakan uji korelasi product moment dengan bantuan SPSS 22.0. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara kemandirian belajar dengan hasil belajar matematika siswa kelas VII SMPN 3 Berbah tahun ajaran 2017/2018 karena nilai sig (2-tailed) 0,023< 0,05. The relation between independent learning with the result of math studying Abstract The purpose of this research is to to find out the relation between independent study and the student’s result of Math studying at 7th grade SMPN 3 Berbah. This research is regarded as Quantitative research. The population of this particular research is the students of 7th grade SMPN 3 Berbah as a whole, which has 4 classes with the total of 127 students. The sample which is used in this research are as many as 96 students. The technique of retrieving the samples used in this research is called simple random sampling. The technique of collecting the data is the questionnaire and documentation. Hypothesis test using product moment test with SPSS 22.0. The result of this research reveals that It has been found that there is a positive relation which is significant between independent studying and the result of Math studying at 7th grade SMPN 3 Berbah in year 2017/2018 due to sig value (2-tailed) 0,023<0,05.